The gospel of freedom & power Protestant missionaries in American culture after World War II - Ruble, Sarah E. (Chapel Hill : University of North Carolina Press, 2012)
In the decades after World War II, Protestant missionaries abroad were a topic of vigorous public debate. Public conversations about missionaries followed a powerful yet paradoxical line of reasoning, namely that people abroad needed greater autonomy from U.S. power and that Americans could best tell others how to use their freedom. In The Gospel of Freedom and Power, Sarah Ruble analyzes these public discussions about what it meant for Americans abroad to be good world citizens, placing them firmly in the context of the United States' postwar global dominance.
Protestant mainline -- Evangelicals -- Anthropology -- Gender.
Includes bibliographical references (pages 185-204) and index.
Print version record.
Keywords: Missions, American -- History -- 20th century; Protestant churches -- Missions -- History -- 20th century; United States -- Foreign public opinion; United States -- Foreign relations -- Public opinion; United States -- Foreign public opinion; United States -- Foreign relations -- Public opinion; RELIGION -- Christian Ministry -- Missions; International relations -- Public opinion; Missions, American; Protestant churches -- Missions; Public opinion; United States; RELIGION / Christian Ministry / Missions; 1900 - 1999; Electronic books; History